Hierarchical ITO nanofibers coated Mn3O4 nanoplates core-shell nanocomposites for high performance all-solid-state symmetric supercapacitor device. Issue 21 (1st November 2021) - Beknalkar, S.A.; Teli, A.M.; Harale, N.S.; Pawar, K.K.; Patil, D.S.; Shin, J.C.; Patil, P.S.
Abstract: We have made a first attempt to build a novel Tin doped indium oxide@Manganese oxide (ITO@Mn3 O4 ) nanocomposite electrode to overcome the detriments of Mn3 O4 such as low conductivity and small potential window. Herein, we have synthesized the ITO@Mn3 O4 nanocomposite by growing Mn3 O4 nanoplates over ITO nanofibers synthesized by electrospinning technique. Benefitted from, the high conductivity and negative operating potential window of ITO exceptionally increased in the electrochemical performance of ITO@Mn3 O4 was observed. The specific capacitance of optimized ITO@Mn3 O4 nanocomposite reached up to 823 F/g at 1 mA/cm 2 in a wide potential window of 2 V using Na2 SO4 electrolyte. To determine the practical feasibility an ITO@Mn3 O4 //ITO@Mn3 O4 all-solid-state symmetric device was developed, which operated very well in a 2.2 V voltage window. It was found to deliver a maximum energy density of 88 Wh/kg and a power density of 550 W/kg. This novel composite inferred the significance of using simple design to build a high-performance device. Graphical abstract: Image 1